SOSIALISASI PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN PEMASARAN UMKM DI KECAMATAN SUTOJAYAN, KABUPATEN BLITAR - Marinda Sari Sofiyana; Linda Dwi Lestari; Meita Hadi Triamini; Anggi Isna Faizah; Verdha Risang Ardiyansyah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
UMKM is a private business. it is expected to help Indonesian Economic growth. One example of UMKM is Griya Batik Sum Gati located in Sutojayan district. The purpose of this community service activity is to help UMKM of Griya Batik Sum Gaati in the social media-based marketing process. the method used in this community service activity is marketing socialisation on the use of social media such Instagram and facebook. this activity has three steps, they are preparation and planning, activitity implementation, evaluation and monitoring. the result of the community service activity is getting understanding and new experience in product marketing through social media.